Central Poststroke Pain: Its Profile among Stroke Survivors in Kano, Nigeria - Abdulbaki Halliru Bashir; Auwal Abdullahi; Muhammad Aliyu Abba; Naziru Bashir Mukhtar (Behavioural Neurology)
Background. Central poststroke pain (CPSP) caused by sensory dysfunction of central origin is a disabling condition that significantly affects the quality of life of stroke patients. Aim. The aim of this study is to determine the clinical profiles and pattern of CPSP among stroke patients in Kano, Nigeria. Methods. The study was a cross-sectional design involving stroke survivors who were ≥18 years old and with no significant cognitive impairment approved by the Research Ethics Committee of Aminu Kano Teaching Hospital. Participants were assessed using diagnostic criteria form, the douleur neuropathique 4 questions (DN4 questionnaire), and Leeds assessment of neuropathic symptoms and signs (LANNS). Results. A total of 120 stroke patients participated in the study, in which 6 (5%) were diagnosed with CPSP occurring within the first 3 months in 50% of the participants. The pain characteristics were mainly moderate (83.3%), burning (62.5%), and continuously experienced (66.7%). The frequently affected parts were extremities or occurring as hemisyndrome. Conclusion. Prevalence of CPSP following stroke is low. The clinical features are variable and can occur at a varied time and different intensities and locations. However, it majorly occurs within the first few months post stroke.